The Effects of Different Administration Regimens of Berberine Hydrochloride on the Pharmacokinetics of Sirolimus in Rats - Yuanxia Yang; Yue Zhang; Yingdong Qu; Liwan Cui (Pharmacology Research & Perspectives)
ABSTRACT Sirolimus is a third‐generation immunosuppressant with multiple efficacies, including antifungal, antitumor, and immunosuppressive properties. We conducted a pharmacokinetic study to determine the effect of berberine hydrochloride (BBR) on the pharmacokinetics of sirolimus in rats. Thirty‐six rats were randomly divided into six groups, and blood samples were collected from the posterior orbital venous plexus at different time points after the last administration to determine the plasma concentration of sirolimus. Liquid chromatography tandem mass spectrometry (LC–MS/MS) was used for detection, and DAS 2.0 software was employed for pharmacokinetic analysis. A single administration of BBR significantly reduced the pharmacokinetic parameter AUC0‐12h of sirolimus. Repeated administration of BBR resulted in an upward trend in Cmax AUC0‐12h, AUC0‐∞, and CLz all show an upward trend. This study indicates that BBR has a certain impact on the pharmacokinetics of sirolimus in rats. However, further validation of the role of gene polymorphism in pharmacokinetics and clinical efficacy is needed for further research in a wider population.